1999
DOI: 10.1080/002689799165729
|View full text |Cite
|
Sign up to set email alerts
|

Transverse wavevector dependent and frequency dependent dielectric function, magnetic permittivity and generalized conductivity of interaction site fluids: MD calculations for the TIP4P water

Abstract: It is shown that the dielectric properties of interaction site models of polar fluids can be investigated in computer experiment using not only the charge fluctuations but also correlations corresponding to a current of moving charges. This current can be associated with a generalized dynamical polarization or separated into electric and magnetic components. The first approach deals with the dielectric permittivity related to a generalized conductivity, whereas the second one leads to the functions describing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studying TIP4P water, the same author showed that for interaction site models a different approach, based on current correlations, 118 is more appropriate. 119 Sutmann derived a generalized fluctuation dissipation theorem, which accounts for different types of boundary conditions in MD simulation. 120 Essex claims that the Monte Carlo method with reaction-field treatment of the long-range interactions is superior to molecular dynamics for the simulation of the static permittivity.…”
Section: General Principles and Model Systemsmentioning
confidence: 99%
“…Studying TIP4P water, the same author showed that for interaction site models a different approach, based on current correlations, 118 is more appropriate. 119 Sutmann derived a generalized fluctuation dissipation theorem, which accounts for different types of boundary conditions in MD simulation. 120 Essex claims that the Monte Carlo method with reaction-field treatment of the long-range interactions is superior to molecular dynamics for the simulation of the static permittivity.…”
Section: General Principles and Model Systemsmentioning
confidence: 99%
“…The choice of a relatively simple fluid of HSCs allowed us to run extensive MC simulations (0.6−0.8 million production cycles) with 800 solvent molecules and directly generate the Fourier transform of the polarization response function χ αβ ( k ) (the details of the simulation procedure will be published elsewhere 11 ). The polarization response function poorly converges in computer simulations,12a and it is hard to obtain for more complex model fluids. 12b,c,d χ αβ ( k ) is inaccessible experimentally and has been studied only theoretically for a few model isotropic fluids. , This is the first calculation of the polarization correlation function performed in a nematic solvent.…”
Section: Modelmentioning
confidence: 99%
“…The response function obtained from computer simulations is used to calculate the solvent reorganization energy according to the equation 9 In eq 2, χ L ( k ) = ∑ α , β k̂ α χ αβ k̂ β is the longitudinal response function ( k̂ α are the Cartesian components of the unit wave-vector k̂ ). χ L ( k ) represents the solvent response to a spherically symmetric (longitudinal) solute field. , This type of the solute electric field is employed in the Marcus two-sphere configuration 7a modeling the DAC as two spheres of radii R D (donor) and R A (acceptor) separated by the distance R > R D + R A (intermolecular ET) 7a. The Marcus configuration with R A = R D = 4 Å and R = 10 Å is adopted here for the calculations of λ s .…”
Section: Modelmentioning
confidence: 99%
“…(2) macroscopic continuum limit (q = 0) ≡ = 1 + 1/κ and the correct limit (q → ∞) = 1. If the solvent is water or, more generally, a polar fluid, however, model calculations [7], neutron diffraction experiments and atomistic molecular dynamics simulations [8][9][10] have shown that the form of (q) is more complicated. Before decaying to 1 at large wavevectors, the dielectric function passes through two poles, and in between lies a band of negative values.…”
Section: Introductionmentioning
confidence: 99%